Does fiscal decentralization foster regional investment in productive infrastructure? - Andreas Kappeler; Albert Solé-Ollé; Andreas Stephan; Timo Välilä (European Regional Science Association (ERSA), 2012)
Spending on productive infrastructure is seen as an important contributor to long term economic growth. Several authors have documented a downward trend in public investment during the last three decades and warned about its possible detrimental effects on the economy. A not well-realized fact is that productive infrastructure investment is mostly provided by sub-national governments. The aim of this paper is to analyze the effect of revenue decentralization on the provision of infrastructure at the sub-national level. We estimate the effects of revenue decentralization and earmarked grant financing on the level of sub-national infrastructure investment in 20 European countries over the period 1990-2009. The findings are compared to those obtained when using sub-national investment in redistribution, for which the theory predictions are different. To account for the high auto-correlation in the dependent variable, we apply a dynamic panel data approach. In particular, we use a Corrected Least Squares Dummy Variable (LSDVC) estimator with the lagged dependent variable included to account for the dynamic character of the dependent variable. The empirical analysis shows that decentralisation in terms of tax shares increases public investment in infrastructure; public investment in redistribution is not significantly affected by decentralisation. The positive link between total regional investment and decentralisation suggests that decentralisation on regional infrastructure investment is additional and does not go hand in hand with a considerable reduction in other types of regional investment, such as health, education or safety. As to investment grants, they have a positive impact on both types of regional investment. The negative interaction between investment grants and decentralisation for regional infrastructure investment suggest that the impact of tax decentralisation on regional infrastructure investment declines with increasing receipts of investment grants by regional governments. This result is intuitive. As the significance of the tax-decentralisation parameter suggests, higher regional decision autonomy leads to more investment in infrastructure. Attempts to undermine the power of regions through the backdoor - e.g. by introducing conditional transfers - will at least partly offset the positive effect of decentralisation.
Keywords: 330